Aplikasi Sistem Informasi Geografi untuk Kajian Fluktuasi Muka Air Tanah dan Karakteristik Akuifer di Kawasan Kecamatan Denpasar Timur Kota Denpasar - BUANA, PUTU SINTAYANI; WIYANTI, WIYANTI; SUYARTO, R. (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Application of Geographic Information System for Study of Water Table Fluctuations and Characteristics of Aquifers in the East Denpasar Subdistrict Region Denpasar City   The growth of development and population in East Denpasar causing domestic water are increasing. In the other hand the water supply from Water Supply Company (PDAM) has not been able to serve all the needs of the community, so they use another alternative form of groundwater extraction. The increased water demand from groundwater causing groundwater degradation which is reflected by the decreasing quality and water table fluctuation level. This research aims to determine the fluctuations and depth distribution of water table, flow direction and characteristics of aquifers. The method used is survey method and analyzed with descriptive quantitative. Spatially the data is presented with Geographic Information Systems (GIS) using ArcGIS software. The results showed that the depth of the water table in the dry season ranged from 0,74-24 m and the rainy season ranged from 0,15-15,82 m with a range of water table fluctuations is 0,59-8,18 m. The flow direction of groundwater moves from north to south and partly inclines to southeast or southwest with an angle greater than N 185° E. The types of aquifers found were unconfined aquifers up to a depth of 160 m and the rock constituent material form of sand/sandstone, compact sand, loose sand, clay sand, volcanic ash/tuff and gravel.